Association of Atherogenic Index of Plasma with Stroke Subtypes: A Hospital-Based Study - Baral, Sharad Chandra; Shrestha, Surendra Lal; Gajurel, Sharad Hari (Annapurna Journal of Health Sciences, 2026)
Introduction: Strokeis the second leading cause of death worldwide, affects about 15 million people annually. While secondary prevention of atherosclerotic stroke (AS) mainly focuses on lowering LDL-C with statins, the roles of triglycerides (TG) and HDL-C remain unclear. The atherogenic index of plasma (AIP) may help explain this relationship. This study aimed to assess the association between AIP and stroke. Methods: A hospital-based retrospective study was conducted at Bir Hospital from May to December 2019 using consecutive non-probability sampling. Sixty adult stroke patients were classified as cerebral infarction, lacunar infarction, or intracerebral hemorrhage based on non-contrast CT findings. Lipid profile (TC, TG, HDL-C) was measured using an automated photometric analyzer, and LDL-C was calculated using the Friedewald formula. Measurements were obtained within 24 hours of stroke onset or after 12 weeks. AIP was calculated as log10(TG/HDL-C). Ethical approval was obtained from the Institutional Review Board of National Academy of Medical Sciences, and data were analyzed using SPSS version 22.0 with Chi-square and Fisher’s exact tests. Results: Higher AIP levels were more associated with lacunar infarction than other stroke types and correlated with LDL-C in these patients. Hypertension was associated with higher AIP in lacunar infarction, while no association was observed between AIP and BMI. The mean patient age was 61.6 ± 16.5 years (range 26–99), with a higher incidence of stroke in males than females. Conclusions : Lacunar infarction showed a stronger association with the atherogenic index of plasma (AIP). AIP demonstrated a significant negative correlation with LDL-C in patients with lacunar infarction. High-risk AIP levels were observed in a minority of patients with smoking history and hypertension.